Development of Learning Object Materials for Multimedia Learning Integrated with Dompu Local Wisdom for Students - Prayudi, Andi; Supriyaddin, Supriyaddin; Burhanuddin, Burhanuddin; Akhirwan, Akhirwan; Rasul, Abdul (FKIP - Universitas Riau, 2025)
This study is motivated by the fact that the learning process of the Instructional Multimedia course still relies on printed (non-digital) textbooks and does not sufficiently foster students’ analytical and problem-solving skills, either individually or in groups. As a result, students’ competence in developing instructional multimedia has not shown significant improvement. This condition is attributed to the previously used learning materials, which were less practical and ineffective when applied in a course that requires intensive case analysis, problem-solving, assignments, and practicum activities. The objective of this study is to develop Learning Object Materials based on the Case Method and Team-Based Project, integrated with Dompu local wisdom, that are valid, practical, and effective. This research employed a Research and Development (R&D) method, adopting the 4-D (Four-D) Model by Thiagarajan, consisting of four stages: define, design, develop, and disseminate. The validation results indicate that the developed product achieved an average score of 4.2 (valid category), respondent score of 4.13 (practical category), and an N-Gain percentage of 58% (moderately effective category). Thus, the product is considered feasible to be implemented as an alternative Learning Object Material to enhance the quality of learning.